Profil glucido-lipidique et risque cardiovasculaire chez les diabétiques de type 2 - Mourad Nachi; Ibtissem Kihel; Abdessamad Dali-Ali; Mouna Gourine; Fouzia Benrahal (Journal de la Faculté de Médecine d'Oran)
Abstract Background-Diabetes is a real health public problem because of its many potential complications, particularly the cardiovascular ones.The aim of this work was to describe the clinical and biological profile in type 2 diabetic population, then to study the relationship between glycemic control and lipid abnormalities with micro and macro vascular complications. Methods - It was about a retrospective study of 341 type 2 diabetes patients’ with an average age of 60.1 ± 11.71 years.The IBM® SPSS statistics 20.0 software was used for analyzing data. Only significant associations (p ≤ 5%) were retained. Results -An HbA1c level ≥7% was observed in 82,5% of patients, More than 60% have dyslipidemia. 52,8% of them have an LDLc level ≤ 1 g/l, and 64,4% have a Non-HDLc level >1g/l. Sixty-six percent of patients have high blood pressure. The macrovascular disorders were observed on 30,9% of patients and microvascular ones on 66,8% of them (p = 0.0001).The logistic regression analysis showed that HbA1c was the most significant biological parameter (p=0,008).while for micro-vascular complications, high blood pressure was the only associated factor (p = 0.03). For ischemic heart disease, dyslipidemia and high blood pressure were the most associated factors. Conclusion - this study showed a high frequency of micro and macrovascular complications, lipid abnormalities and a very poor glycemic control. The elevation of HbA1c level, the high blood pressure and dyslipidemia are the most associated factors with a high cardiovascular risk.